TRADITIONAL USES OF WILD BERRIES IN THE BUKOVINA REGION (ROMANIA) - Ana LEAHU (Stefan cel Mare University of Suceava, 2019)
In recent years there has been given increased attention to the health-promoting dietary recommendations as regards the use of wild berries in human nutrition. This study analyzes the differences in the consumption of wild berries in the Bukovina area (in the northern part of Romania). Bilberries (Vaccinium myrtillus L.), sea-buckthorn (Hippophae rhamnoides L), rosehip (Rosa Canina L.) and hawthorn (Crataegus monogyna L.) are the plants harvested from spontaneous flora, with diverse uses, such as preparation of juices, tinctures and decoctions or tea beverages due to their medicinal and nutritional potential. Wild berries are also processed for production of beverages, jams, as functional food products, and, to some extent, they are consumed fresh as well. The consumers’ preferences were established by the analysis of questionnaires of 101 respondents interviewed concerning different botanicals used in a particular geographical and cultural context. The results show that the selections of wild berries containing many biochemical compounds are mostly used as teas or decoctions due to their nutritional role and health benefits. The preference for sea-buckthorn (Hippophae rhamnoides L) was strongly associated with its dietary benefits for the immune system. The consumption of wild berries is considered important by the Romanians living in Bukovina in fresh form, as beverages or in the dried form.